Chronic thromboembolic disease following pulmonary embolism: time for a fresh look at old clot. Issue 4 (2nd April 2020) - McCabe, Colm; Dimopoulos, Konstantinos; Pitcher, Alex; Orchard, Elizabeth; Price, Laura C.; Kempny, Aleksander; Wort, S. John
The recently updated European Society of Cardiology/European Respiratory Society guidelines for acute pulmonary embolism (PE) underline the importance of appropriate long-term management of PE sequelae in the era of extended anticoagulation [1]. Chronic thromboembolic disease (CTED) is one of several conditions contributing to breathlessness in this setting, i.e. persistent pulmonary vascular obstruction on imaging, with no evidence of pulmonary hypertension at rest. CTED is increasingly encountered in pulmonary vascular disease clinics following acute PE, and its diagnosis relies heavily on careful exclusion of other conditions that may contribute to symptoms. Chronic thromboembolic disease diagnosed following acute pulmonary embolism warrants refinement of its definition and further evaluation of optimal anticoagulation strategies http://bit.ly/38SQXc0